Review of Sebadexius Ledoyer, 1984 (Amphipoda, Dexaminidae, Dexamininae) based on new material from The Philippines, with Sebadexius cebuense sp. nov. - Just, Jean (Zootaxa, 2018)
The amphipod genus Sebadexius Ledoyer, 1984 (New Caledonia) is reviewed, based on new material from Cebu in The Philippines. Some characters are re-interpreted, and a new species, Sebadexius cebuense, is described.